First presentation of acute intermittent porphyria with steroid-responsive encephalopathy associated with autoimmune thyroiditis - M. W. K. De Zoysa; W. Uluwattage; E. Jasinge; E. W. B. Edirisinghe (Asian Journal of Internal Medicine)
Steroid responsive encephalopathy associated with autoimmune thyroiditis (SREAT), also called Hashimoto’s encephalopathy (HE), a treatable disease, has a wide spectrum of clinical presentation and is therefore, often misdiagnosed. Acute intermittent porphyria (AIP) is a rare disease and its prevalence in Sri Lanka is unknown. Coexistence or precipitation of AIP with thyroid illness is reported mainly related to hyperthyroidism. Here we report a case of a young girl who presented with abdominal pain, seizures, hypertension, hyponatraemia and subtle features of hypothyroidism who was successfully treated for SREAT with first AIP flare. This case highlights the possibility of coexistence of two rare entities in a single patient.